2016
DOI: 10.3390/en9121009
|View full text |Cite
|
Sign up to set email alerts
|

Development of Correlations for Windage Power Losses Modeling in an Axial Flux Permanent Magnet Synchronous Machine with Geometrical Features of the Magnets

Abstract: Abstract:In this paper, a set of correlations for the windage power losses in a 4 kW axial flux permanent magnet synchronous machine (AFPMSM) is presented. In order to have an efficient machine, it is necessary to optimize the total electromagnetic and mechanical losses. Therefore, fast equations are needed to estimate the windage power losses of the machine. The geometry consists of an open rotor-stator with sixteen magnets at the periphery of the rotor with an annular opening in the entire disk. Air can flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The windings were excited by a fixed DC current to get controlled losses and to eliminate the stator core losses. The mechanical losses are calculated using equations in [24]. The mechanical losses are lumped and injected in the PM node in the rotor LPTN model.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The windings were excited by a fixed DC current to get controlled losses and to eliminate the stator core losses. The mechanical losses are calculated using equations in [24]. The mechanical losses are lumped and injected in the PM node in the rotor LPTN model.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The aerodynamic forces acting on rotary parts of the machine cause mechanical losses in the surfaces exposed to it. Extensive CFD simulations and curve fittings done in [24] have found accurate and parametrized formulas for the windage losses on every surface. These formulas are used to calculate the mechanical losses.…”
Section: Mechanical Lossesmentioning
confidence: 99%
“…Although this research was conducted in the field of oceanography, its application can be extended to geophysics, astrophysics, and turbomachinery. Apart from localized differences, it has been shown that the general flow field in an AFPM machine is similar to a simplified rotor-stator configuration [4][5][6] to which the generic theory of Ref. [3] applies.…”
Section: Flow Characteristicsmentioning
confidence: 99%
“…Although it would be favorable to include such three-dimensional features, this is impractical from a computational effort point of view. Based on results reported in the literature, it is expected that the axisymmetric model will result in similar flow and heat transfer structures compared to the three-dimensional case [4,64].…”
Section: Afpm Simulation Setupmentioning
confidence: 99%
“…Investigations into windage losses for large gaps and atmospheric air have been the subject of numerous studies [11]. Numerous researchers have started using CFD numerical simulations in conjunction with experiments in recent years [12]- [16]. In a vacuum chamber, Walton et al [10] investigated the windage losses of a rotor supported by gas foil bearings, but they did not consider the fluid field's impact near the journal.…”
Section: Introductionmentioning
confidence: 99%